Factor analysis of low of the students' interest in Aceh Utara and Lhokseumawe Regencies to continue education in the Mathematics Tadris Department of IAIN Lhokseumawe - Setiawan, Setiawan; Azmi, Nur (International Journal of Trends in Mathematics Education Research, 2023)
The growth in interest of SMA/MA graduates spread across Lhokseumawe City and Aceh Utara Regency has greatly decreased in interest in the IAIN Lhokseumawe Mathematics Tadris Department. This decline in interest can be seen in the decline in the number of students in this department from year to year over the last 5 years. The aim of this research is: To examine students' views, the factors causing low student interest and efforts to increase the interest of prospective new students in the Tadris Mathematics Department. The type of research used in this research is descriptive qualitative. The research objects were high school and MA class XII students in Lhokseumawe City and Aceh Utara Regency. The results obtained show that students' views on the Tadris Mathematics Department are 1) students do not know about the Tadris Mathematics Department, 2) students do not like mathematics subjects, 3) students do not understand that the Tadris Mathematics Department is a department that prepares prospective mathematics teachers. Furthermore, the factors that cause students' low interest in continuing their education at the Tadris Mathematics Department are 1) lack of information, 2) dislike of the teaching profession, 3) not being a favorite choice, 4) considering that mathematics is a difficult subject. The efforts to increase the interest of prospective new students to enter the Tadris Mathematics Department are 1) optimal introduction to the Department, 2) increasing accreditation, 3) demonstrating the uniqueness of the Department, 4) providing training in using applications appropriate to the department.